Assessment of the impact of motor development on adaptation to learning - Kiparenko, Olena Leonidivna; Kremenchutska, Margaryta Kostyantynivna (Insight: the psychological dimensions of society, 2021)
The article renders findings of the study of the developmentof school children’s reading skills and motordevelopment (n=61). Pedagogical and psychologicalliterature considers visual, auditory, and cognitiveimpairments as primary causes of difficulties in developingreading skills. It is generalized an idea that alltypes of perception (visual, auditory, etc.) are of afferent-efferent nature: each of these sensory processesis based on its own motor components. The purposeof the research is to analyze the impact of student’smotor skills disorders on mastering reading skills; to find the root of the disorders using neuropsychologicaltests; to differentiate errors and identify effective correctionmethods. Research methods are as follows:O. Luria Neuropsychological Battery adapted to schoolchildren by Glozman J.; child dyslexia test by O. Korniev& O. Ishymova. Research results have been processedthrough mathematical statistics, i.e., Pearsoncorrelation coefficient and point-biserial correlationcoefficient. Results. It has been identified the mostsignificant indices of the functioning of the motor systemof a child, which influence the progress of masteringreading skills in two age groups of school children(aged 7-9 and 10-12). The research has found the mostfundamental errors made by school children while performingtests that are a ground for basic neuropsychologicalcorrection. Conclusions. It has been substantiatedthat reading is a multi-factor process, and helpinga pupil under some reading difficulties. It cannot be limitedto monotonous methods. The research states thatneuropsychological diagnostics contributes to findingpoorly-developed elements, which affect a child’slearning, discovering errors, and developing an effectiveintervention plan. The first step of the correctionshould comprise the work with the child motor system,as proved by this research. It is noted that a sensorimotorcorrection based on M. Bernstein’s constructionof movements may underly the program.